Natural enemies of major insect pests of black pepper (Piper nigrum L.) in India - KOYA, S DEVASAHAYAM, K M ABDULLA (Journal of Spices and Aromatic Crops, 1994)
The natural enemies recorded on major insect pests of black pepper (Piper nigrum L.) in India including new records are given. The potential of utilising them in biological control programmes are discussed.